Bridging distance through zooming? The use of virtual assignments in multinational corporations - Wicht, Luisa; Holtbrügge, Dirk (Journal of Global Mobility, 2023)
Purpose: Virtual assignments, in which the virtual assignees do not relocate to host locations, but work remotely, have several advantages compared to traditional international assignments, such as enhanced flexibility, cost-efficiency and the possibility that virtual assignees can stay in their home communities. However, it is open to question whether virtual assignments are as effective as traditional assignments. The purpose of this study is to compare the ability of virtual vs traditional assignees to bridge the distance between headquarters and subsidiaries. Design/methodology/approach: Based on a survey among virtual and traditional assignees, the ability to bridge multiple facets of distance is examined. Findings: The results indicate that virtual and traditional assignees have similar abilities to bridge geographic, cultural, functional and language distance. However, traditional assignees have a higher ability to bridge emotional and temporal distance. Originality/value: By applying the distance framework to virtual assignments, a new theoretical perspective is introduced and the importance of clearly disentangling distance-bridging abilities is highlighted. One practical recommendation is that, due to lower costs and reduced coordination efforts required for virtual assignments, this assignment type is preferable if the cultural, language, functional and geographic distances are the most problematic ones during international assignments.
CRIS-Team Scopus Importer:2023-04-14
Keywords: Distance framework; Expatriates; Global virtual work; International assignments; Virtual assignments; Virtual global mobility; Kulturelle Vielfalt

Developing human resources for international activities: The case of Leoni - Heidemann, Christina; Wicht, Luisa; Holtbrügge, Dirk (Nomos Verlagsgesellschaft mbH und Co KG, 2024)
CRIS-Team Scopus Importer:2025-02-04

The use and usefulness of artificial intelligence in international business education. Evidence from a field study - Holtbrügge, Dirk; Wicht, Luisa; Bernhard, Theresa (International Journal of Management Education, 2025)
This field study is among the first empirical investigations into the integration of an artificial intelligence (AI) enhanced video course in management and international business (IB) education. Moving beyond conceptual discussions, it evaluates the use and perceived usefulness of an AI-enhanced video course in a real classroom setting. Findings highlight that such AI tools support personalized learning, increase student engagement, and offer particular benefits for culturally diverse learners by reducing communication barriers and accommodating different educational backgrounds. While exploratory in scope, the study offers practical insights for educators seeking to implement AI in an inclusive and effective manner. Limitations include reliance on self-reported perceptions and a focus solely on student experiences. Future research should examine the impact of AI on learning outcomes and explore the reasons for using AI tools further, for example by investigating emotional and affective components.
CRIS-Team Scopus Importer:2025-09-12
Keywords: Artificial intelligence; Educational videos; Field study; International business education; Personalized learning; Usage; User satisfaction